Mejoramiento del proceso de adquisiciones corporativas - Navarrete Galarza, Yessenia (2009)
This project details to the development and implementation of the system of corporative purchases that will allow the company to optimize its acquisition processes through the just in time delivery product asked for the different Divisions and Departments of the organization, this project was implemented with workflow, explaining the benefits, characteristics of the product, activities schedule, control of advances, explaining about control of risks, administration of human resources involved in the project from directive levels to the operative levels and establishing the expectations for each one of them, contract administration of consultant's offices, establishing political and procedures, as well as the importance of management of communications. Here specifies the activities that are made in each one the phases of the project which they are analysis of necessities, beginning of the project, plan of the project, development, implementation and closes, the same ones which they are based on methodology PMBOK.